Synchronization of Interacting Quantum Dipoles - Herrera-Urbina, F (Institute of Physics Publishing, 2015)
Macroscopic ensembles of radiating dipoles are ubiquitous in the physical and natural sciences. In the classical limit the dipoles can be described as damped-driven oscillators, which are able to spontaneously synchronize and collectively lock their phases in the presence of nonlinear coupling. Here we investigate the corresponding phenomenon with arrays of quantized two-level systems coupled via long-range and anisotropic dipolar interactions. Our calculations demonstrate that by incoherently driving dense packed arrays of strongly interacting dipoles, the dipoles can overcome the decoherence induced by quantum fluctuations and inhomogeneous coupling and reach a synchronized steady-state characterized by a macroscopic phase coherence. This steady-state bears much similarity to that observed in classical systems, and yet also exhibits genuine quantum properties such as quantum correlations and quantum phase diffusion (reminiscent of lasing). Our predictions could be relevant for the development of better atomic clocks and a variety of noise tolerant quantum devices. © 2015 IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.